Pengaruh Metode Pembelajaran Mind Mapping terhadap Hasil Belajar Siswa SMP Kristen Ta’Aba pada Mata Pelajaran IPS - Yanto Yanuarius Seran; Wolfgang Asindo Seran; Ivony Sarlin Asa (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Social studies learning as one of the progmatic components in the school curriculum is actually expected to support the achievement of the ideal goals of education. Through social studies education, students are fostered and developed their intellectual mental abilities to become citizens who are skilled and socially concerned and responsible in accordance with the values contained in Pancasila. Social studies learning contained in the educational curriculum is a simplification of learning materials from social science knowledge or concepts. The method in this study is research using a quantitative research approach. This research is descriptive. The sample in this study was 30 students of grade VIIIA (control) and VIIIB (experiment) of SMP Kristen Taaba District. Data collection techniques using test questions and documentation. Based on the results of research and discussion, and data analysis carried out, it can be concluded that the mind mapping learning model can affect the learning outcomes of social studies class VIII SMP Kristen Taaba District. Indicators of the assessment of learning outcomes can be seen from the students' posttest scores have increased. Based on the research objectives with the t-test hypothesis, an sg (2 – Tailed) value of < 0.05 is obtained which is 0.000 so that H0 is rejected meaning that there is an influence of the mind mapping learning model on the learning outcomes of social studies class VIII SMP Kristen Taaba District. In other words, the mind mapping learning model affects learning outcomes with categories that are quite effective.